Changes in leg strength 8 and 32 h after endurance exercise - Leveritt, M.; MacLaughlin, H.; Abernethy, P. J. (Journal of Sports Sciences, 2000)
The aim of this study was to determine the effects of a single bout of endurance exercise on subsequent strength performance. Eight males with a long history of resistance training performed isokinetic, isometric and isotonic leg extension strength tests 8 and 32 h after 50 min of cycle ergometry at 70-110% of critical power. The participants also completed a control condition in which no cycling was performed. Plasma lactate and ammonia were measured before and immediately after each strength test. Isokinetic, isometric and isotonic leg extension torques were not significantly different 8 or 32 h after endurance exercise compared with the control condition (P > 0.05). A large (50.3%), but not statistically significant, increase in plasma ammonia was evident during the strength tests performed 8 h after endurance exercise, while a significant (P < 0.05) increase in ammonia was also seen 32 h after endurance exercise. No significant changes in plasma ammonia were evident in the control condition. Our results suggest that leg extension strength was not compromised by an earlier bout of endurance cycling. However, metabolic activity during the strength tests might have been altered by the preceding bout of endurance exercise.